Case study of the constraints and potential contributions regarding wind curtailment in Northeast China. (1st September 2016) - Xiong, Weiming; Wang, Yu; Mathiesen, Brian Vad; Zhang, Xiliang
Abstract: The wind power industry in China is faced with the obstacle of ineffective use due to severe wind curtailment recently. With detailed representation of the electricity and heat sectors in an energy-system-modeling tool, we evaluated the potential of technical improvements that could be implemented to increase wind integration in Northeast China. First, different regulation modes are compared and analyzed. Then, sector integration between the heat and electricity sectors is simulated assuming heat storage and large-scale heat pump utilization. While current regulation rules hamper wind integration, there are no apparent technical barriers to ramp up/down more flexible for wind power generation in Northeast China. The results also indicate that the implementation of heat storage and heat pump could enhance the flexibility of an energy system, making it able to accommodate an increase of wind penetration. Thus, more flexible dispatch rules and integration between the electricity and heating sectors are believed as mature technical solution to increase wind integration in Northeast China. Highlights: Wind curtailment is quantified in detailed energy system modeling in Northeast China. Current regulations regarding electricity generation restrict wind power integration. Use of heat pumps and heat storage could help increase rate of wind penetration.